Keputusan Pembelian Merek Handphone di Kalangan Mahasiswa D3 Marketing Universitas Sultan Ageng Tirtayasa - Arum Wahyuni Purbohastuti (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to determine the factors that influence mobile brand purchasing decisions. Where The object of research is Student D3 Marketing University of Sultan Ageng Tirtayasa force year 2014. The method used in this study is a qualitative method of research that is descriptive and tend to use analysis. The samples taken were saturated samples because the total population was sampled by 44 students. Based on the research that has been done, the decision to purchase handphone brand among D3 Marketing students is influenced by several factors such as brand image, quality, price, features, warranty, access to get, needs, family factor.